(2y-1)(8-y)=0

Simple and best practice solution for (2y-1)(8-y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2y-1)(8-y)=0 equation:


Simplifying
(2y + -1)(8 + -1y) = 0

Reorder the terms:
(-1 + 2y)(8 + -1y) = 0

Multiply (-1 + 2y) * (8 + -1y)
(-1(8 + -1y) + 2y * (8 + -1y)) = 0
((8 * -1 + -1y * -1) + 2y * (8 + -1y)) = 0
((-8 + 1y) + 2y * (8 + -1y)) = 0
(-8 + 1y + (8 * 2y + -1y * 2y)) = 0
(-8 + 1y + (16y + -2y2)) = 0

Combine like terms: 1y + 16y = 17y
(-8 + 17y + -2y2) = 0

Solving
-8 + 17y + -2y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(-8 + y)(1 + -2y) = 0

Subproblem 1

Set the factor '(-8 + y)' equal to zero and attempt to solve: Simplifying -8 + y = 0 Solving -8 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + y = 0 + 8 y = 0 + 8 Combine like terms: 0 + 8 = 8 y = 8 Simplifying y = 8

Subproblem 2

Set the factor '(1 + -2y)' equal to zero and attempt to solve: Simplifying 1 + -2y = 0 Solving 1 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2y = 0 + -1 -2y = 0 + -1 Combine like terms: 0 + -1 = -1 -2y = -1 Divide each side by '-2'. y = 0.5 Simplifying y = 0.5

Solution

y = {8, 0.5}

See similar equations:

| 20+(3x)=32-x | | -8x+3=-3-6 | | 15+(5-x)=30/x | | 3m/2 | | 4-1/(2(x^1/2))=0 | | 5x+2.5=3 | | (z-4)(z-8)=0 | | 4-(1/2(x^1/2))=0 | | 7/8=42/48 | | 20+(3x)=12-x | | 0=55.0mph+a(4.17) | | 4-1/2(x^1/2)=0 | | 11-3x/4=2x-4 | | 6x+4-2x+10=5x+8 | | 10+x=2x+20 | | 0.042*32= | | 8x=(x^3)+(3x^2) | | 16/F=8 | | 0=55.0+a(4.17) | | E-464=-456 | | D+16+200+64=280 | | 24uv^5w^3-28u^6v^9=0 | | (C+2)(4+6)=40 | | .75(12c-4)=15c+15 | | 9.5=t+3.7 | | -x-4x=-6+3 | | -s-4+6s+4=5 | | n^2-n-584=0 | | 3x=4x-((4*x)*.0285) | | (-2/7)x(-7/9) | | 16(B+4)=64 | | -6(1+3n)=174 |

Equations solver categories